2021
DOI: 10.1007/s00277-021-04413-2
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord blood transplantation can overcome the poor prognosis of KMT2A-MLLT3 acute myeloid leukemia and can lead to good GVHD-free/relapse-free survival

Abstract: This is a retrospective study comparing the effectiveness of umbilical cord blood transplantation (UCBT) and chemotherapy for patients in the first complete remission period for acute myeloid leukemia with KMT2A-MLLT3 rearrangements. A total of 22 patients were included, all of whom achieved first complete remission (CR1) through 1–2 rounds of induction chemotherapy, excluding patients with an early relapse. Twelve patients were treated with UCBT, and 10 patients were treated with chemotherapy after 2 to 4 cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…HSCT is one of the major consolidation therapies for pediatric AML with adverse factors. Most current evidence supported that HSCT could improve the outcomes of pediatric KMT2A ‐r AML 25 , 26 . Nonetheless, our findings indicated that only individuals categorized as high‐ and intermediate risk according to our prognostic system could potentially benefit from HSCT in CR1.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…HSCT is one of the major consolidation therapies for pediatric AML with adverse factors. Most current evidence supported that HSCT could improve the outcomes of pediatric KMT2A ‐r AML 25 , 26 . Nonetheless, our findings indicated that only individuals categorized as high‐ and intermediate risk according to our prognostic system could potentially benefit from HSCT in CR1.…”
Section: Discussionmentioning
confidence: 58%
“…Most current evidence supported that HSCT could improve the outcomes of pediatric KMT2A -r AML. 25,26 Nonetheless, our findings indicated that only individuals categorized as high- and intermediate risk according to our prognostic system could potentially benefit from HSCT in CR1. Given the elevated therapy-related mortality associated with HSCT and its impact on long-term quality of life, the candidates and timepoint to receive HSCT should be carefully considered.…”
Section: Discussionmentioning
confidence: 99%
“…As for other stem cell sources in allo-HSCT, umbilical cord blood transplantation in China also provides more choice for patients. [ 94 , 95 ] Moreover, based on the mechanism of HSCT, microtransplantation may bring hope for older patients with AML who are unfit for HSCT. [ 96 , 97 ]…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the proportion of Chinese guidelines/consensus to international guidelines/consensus is increasing to 59.6% and 43.8% about transplantation norms and complication management, respectively. As for other stem cell sources in allo-HSCT, umbilical cord blood transplantation in China also provides more choice for patients [94,95] . Moreover, based on the mechanism of HSCT, microtransplantation may bring hope for older patients with AML who are unfit for HSCT [96,97] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation